Assessing the Academic Performances in Online and Modular Learning among the Junior High School STE Students of Tanauan City Integrated High School - De Chavez, Merryann (SAFE-Network, 2023)
Education is the foundation of society, like technology, which drives globalization and industrialization. Computers are replacing books in education. One click can Google anything. These changes are relevant to COVID 19, the current global situation. Amid the pandemic, government agencies propose online learning for 2020-2021. This study assessed high school students' online and modular learning performance at Tanauan City Integrated High School. The researcher used descriptive quantitative method to determine the online and modular student performance. Pearson r was used to determine the relationship between respondent demographics and student performance. The results show that students' online and modular learning performances vary based on their personal benefits, such as being satisfied with their work and motivated to pass. Online learning received a higher positive (excellent) response for academic performance, class standing, and attendance than modular learning.